ANALYSIS OF THE PRODUCTIVITY LEVELS OF LABOR IN BEAM AND PLATE STRUCTURE WORD IN THE MYZE SUMENEP HOTEL PROJECT - Rafi, M .; Oetomo, Wateno (Fakultas Teknik Universitas Tanjungpura, 2023)
In a construction project, the productivity of the workforce is one of the fundamental factors that plays an important role in the project's success. Lower productivity increases the likelihood of work delays, whereas higher productivity reduces the chances of delays. The purpose of this study is to determine the productivity levels, labour coefficients, and productivity levels based on Labour Utilization Rate (LUR) for the beam and floor slab work in the Myze Sumenep Hotel Project. The method used in this study involved observation and work sampling methods, employing a productivity rating approach. The research findings indicate that the formwork work group has the highest productivity level in the field, with an average of 5,118 m2/person. The productivity levels for beam iron work, plate iron work, and casting work are 86,461 kg/person, 245,064 kg/person, and 7,364 m3/person, respectively. The work calm coefficient for formwork work is found to be 0,019 OH for foremen, 0,096 OH for builders, and 0,096 OH for workers. For beam iron work, the coefficients are 0,001 OH for foremen, 0,005 OH for carpenters, and 0,005 OH for workers. The coefficients for plate iron work are 0,005 OH for foremen, 0,002 OH for carpenters, and 0,002 OH for workers. Finally, for casting work, the coefficients are 0,014 OH for foremen, 0,041 OH for builders, and 0,081 OH for workers. Based on the worker utility factor (LUR) for beam and slab formwork, the average LUR productivity is 82,84%. Beam ironing work has an average LUR of 86,75%, plate iron work has an average LUR of 86,83%, and foundry work has an average LUR of 69,59%. Therefore, the productivity levels are deemed satisfactory as they exceeded 50%.